Implementasi Metode Bil Qolam terhadap Pemahaman Al-Qur’an pada Peserta Didik Madrasah Tsanawiyah Masyhudiyah Gresik - Nurul Widadi (Prodi PAI STIT Raden Santri Gresik, 2024)
This study discusses the problem of low understanding of the Qur'an among students of Madrasah Tsanawiyah Masyhudiyah Gresik. Many students experience difficulties in reading and understanding the content of the Qur'an, which has an impact on their motivation to learn. The purpose of this study is to implement the Bil Qolam method as a solution to improve the understanding of the Qur'an in students. The method used in this study is a qualitative approach with interview, observation, and document analysis techniques. This research involves students who take part in the Qur'an learning program using the Bil Qolam method. The results of the study show that the application of the Bil Qolam method significantly increases students' understanding of the Qur'an. Students are easier to understand and remember the material taught, and show a higher interest in reading the Qur'an. In addition, this method also helps students in understanding the rules of tajweed and the structure of hijaiyah letters. The conclusion of this study is that the Bil Qolam method has been proven to be effective in improving the understanding of the Qur'an among students, so it is recommended to be applied more widely in the learning of the Qur'an in madrasas. Thus, this method can be a good alternative to improve the quality of Qur'an education.